2010
DOI: 10.1111/j.1467-2979.2009.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness monitoring of fish passage facilities: historical trends, geographic patterns and future directions

Abstract: Fishways and other passage facilities frequently prevent or delay the passage of fishes, highlighting the need for effectiveness monitoring. We reviewed the scientific literature from 1960 to 2008 reporting on effectiveness monitoring of fish passage facilities to assess what taxa and life-stages have been studied, the questions that are asked during evaluation, and how these varied over time or by geographic region. We identified 96 peer-reviewed articles of which 68% focused on passage by adult fishes. Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
315
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(324 citation statements)
references
References 129 publications
(173 reference statements)
5
315
2
2
Order By: Relevance
“…We regret that fishways in Brazil continue to be installed without thorough evaluations, using misleading information and based on nebulous goals (Pompeu et al, 2012). It is clear that fish conservation in impounded areas is a complex issue, demanding broader perspectives and sound ecological information Kraabøl et al, 2009;Roscoe & Hinch, 2010). As long as this broader context is neglected, the risk of installing ineffective fish passages remains.…”
Section: Discussionmentioning
confidence: 99%
“…We regret that fishways in Brazil continue to be installed without thorough evaluations, using misleading information and based on nebulous goals (Pompeu et al, 2012). It is clear that fish conservation in impounded areas is a complex issue, demanding broader perspectives and sound ecological information Kraabøl et al, 2009;Roscoe & Hinch, 2010). As long as this broader context is neglected, the risk of installing ineffective fish passages remains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of physiology to fishway science has been limited (Roscoe and Hinch 2010). Recently, some physiological tools have been successful in identifying how fish populations are affected by dams (e.g., Hasler et al 2009) and fishway passage (Pon et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although fishways are a fairly common mitigation strategy to address river fragmentation, they are rarely subject to adequate biological study to determine whether they are successful (Bunt et al 2012). Early studies would deem a facility successful if fish were observed (e.g., captured in traps, documented via video, human observation) reaching the top of a fishway, but that approach does not document individuals that fail to do so (Roscoe and Hinch 2010). More recently, studies of fishway success (mostly using biotelemetry) have begun to focus on quantifying fishway attraction (the proportion of a fish population attracted to the fishway entrance) and passage efficiency (the proportion of fish attracted to the fishway that successfully ascend; Roscoe and Hinch 2010;Noonan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, fish ladders, or a fish passes, have been developed to enable fish to pass such barriers (Roscoe and Hinch, 2010). They are generally built using hard engineering materials, such as concrete, metal, and wood, and occasionally using synthetic materials, such as fiberglass (Katopodis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%